Підвищення енергетичної безпеки електрозабезпечення споживачів ліній електропередач 0,38 кВ із застосуванням системи моніторингу віртуально вимірювальних приладів - Коробка, С. В.; Стукалець, І. Г.; Бабич, М. І.; Сиротюк, С. В.; Скляр, Олександр Григорович; Болтянський, Борис Володимирович; Скляр, Радміла Вікторівна; Korobka, S.; Stukalets, I.; Babych, M.; Syrotyuk, S.; Sklіar, Oleksandr; et al. (Запоріжжя : ТДАТУ, 2024)
UA: Максимально точне визначення місця пошкоджень на повітряних лініях електропередачі є важливим для забезпечення енергетичної безпеки, стабільності енергосистем і надійності електропостачання споживачів. Існують різні математичні методи, які використовуються для цього, зокрема методи відстані до несправності базуються на оцінці параметрів аварійного стану і широко застосовуються в цифрових релейних терміналах захисту та локаторах пошкоджень ліній електропередачі. Ціль статті полягає в аналізі існуючих методів забезпечення енергетичної безпеки роботи ліній електропередач напругою 0,38 кВ в аварійних ситуаціях для визначення місця пошкодження кабелю і оцінки похибки з використанням параметрів аварійного стану. Розроблена методика авторів дозволяє врахувати різноманітні фактори, включаючи похибки вимірювання струмів і напруг в аварійному стані, що суттєво впливають на точність визначення місця несправності повітряних ліній електропередач. Цей підхід дозволяє зменшити час, необхідний для проведення аварійно-відновлювальних робіт, шляхом більш точного визначення місця пошкодження кабелю та розміру оглядової зони. EN: The most accurate determination of the location of damage on overhead power lines is important for ensuring energy security, stability of power systems, and reliability of power supply to consumers. There are various mathematical methods used for this, in particular the distance-to-fault methods are based on the estimation of parameters of the emergency state and are widely used in digital protection relay terminals and power line fault locators. The purpose of the article is to analyze the existing methods of ensuring the energy security of power transmission lines with a voltage of 0,38 kV in emergency situations to determine the location of damage on overhead power transmission lines and estimate the error using parameters of the emergency state. The study successfully fulfilled all the tasks, in particular, it identified the problems of operating overhead power lines with a voltage of 0,38 kV and conducted a more detailed analysis of them. The principle that was considered in the study to create a reliability model that takes into account the influence of the external environment and possible assumptions allows to obtain a comprehensive and more accurate assessment of the reliability of power supply systems operating under the influence of various factors. Reliability indicators must be calculated taking into account the specifics of operation of specific power supply systems. The resulting mathematical model for forecasting can be used to optimize maintenance schedules, repair and prevention of systems. The work also analyzes modern approaches to solving the problems of ensuring a safe and stable electricity supply in order to meet the modern needs of electricity consumers. The developed technique of the authors allows taking into account various factors, including errors in measuring currents and voltages in an emergency state, which significantly affect the accuracy of determining the location of a fault in overhead power lines. This approach allows to reduce the time required for disaster recovery work by more accurately determining the location of the damage and the size of the inspection area.
Enhancement of energy security of electrical supply of consumers of electrical transmission lines of 0.38 kV using the monitoring system of virtual measuring devices
Keywords: вимірювання; міст постійного струму; “Петля Муррея” та “Петля Варлея”; лінія електропередач; measurement; DC bridge; "Murray Loop" and "Varley Loop"; power line